STUDY ON THE THERMAL-MECHANICAL COUPLING FOR DIFFERENT PLATE URBAN RAILWAY VEHICLE WHEELS - WEN YongPeng; ZHENG XiaoMing; SHANG HuiLin; XU XiaoJun; LI Qiong (Jixie qiangdu)
Based on the urban railway transportation vehicle wheel,three kinds of typical wheel plate（ straight plate,single S plate and double S plate） were set up. The study presents the calculation method of structure load and thermal load of the urban railway transportation vehicle wheel,and focuses on the thermal-mechanical coupling performance of the three types of wheel plate under different abrasion,the characteristic of the thermal-mechanical coupling stress is obtained under the thermal-mechanical coupling condition. The results show that three kinds of urban railway wheels are all satisfied with the requirements of fatigue strength; and the double S plate wheel has a better anti-fatigue performance than straight plate and single S plate wheel in the coupling field.